Locomotor and habitat classifications of cercopithecoid postcranial material from Sterkfontein Member 4, Bolt's Farm and Swartkrans Members 1 and 2, South Africa - Elton, Sarah (Bernard Price Institute for Palaeontological Research, 2001)
Much southern African cercopithecoid postcranial material is not associated with craniodental remains. Consequently, this postcranial material cannot be confidently assigned to a particular taxon, with the result that little is known about the locomotor strategies and habitat preferences of specific Plio-Pleistocene cercopithecoids from southern Africa. However, cercopithecoid postcrania can provide important information about habitats that were present at fossil sites, even when the material is not attributed to taxa. In this paper, ecomorphic analysis is used to assign cercopithecoid postcranial material from Sterkfontein Member 4, Bolt's Farm and Swartkrans Members 1 and 2 to one of three habitat/locomotor categories: forest-living arboreal quadrupeds (‘forest arboreal'), open habitat terrestrial quadrupeds (‘open terrestrial') and open habitat cercopithecoids using a mix of arboreal and terrestrial quadrupedalism (‘open mixed'). Cercopithecoids representing all three habitat categories were found in the samples from Sterkfontein Member 4 and Bolt' s Farm, suggesting that monkeys using a range of habitats and locomotor strategies were present at these sites. However, no 'forest arboreal' cercopithecoids were found in the samples from Swartkrans Members 1 and 2, indicating that cercopithecoids at these localities probably depended largely on open habitats. The habitat and locomotor strategy data were also used in combination with locality-based listings of fossil cercopithecoid craniodental remains to suggest possible locomotor strategies for several southern African Plio-Pleistocene cercopithecoid taxa, including Parapapio broomi (possibly 'forest arboreal'), Parapapio jonesi (‘open terrestrial'), Papio robinsoni (‘open terrestrial') and Cercopithecoides williamsi (‘open mixed').
Keywords: cercopithecoidea; postcranial; Plio-Pleistocene; ecomorphology